Osteochondral Autologous Transplantation for Treating Patellar High-Grade Chondral Defects: A Systematic Review. Issue 10 (16th October 2019) - Donoso, Rodrigo; Figueroa, David; Espinoza, Jaime; Yañez, Claudio; Saavedra, Jamil
Background: Patellar cartilage defects account for 34.6% of defects found during routine arthroscopy. These defects pose a challenge in orthopaedic surgery because they have been associated with worse outcomes after surgical repair compared with other chondral lesions within the knee. Purpose: To systematically review the literature for evidence on results of osteochondral autologous transplantation (OAT) for the management of isolated patellar cartilage high-grade defects (International Cartilage Repair Society [ICRS] grade 3-4). Study Design: Systematic review; Level of evidence, 4. Methods: A systematic review of the literature was performed to find studies that addressed outcomes regarding OAT to treat patellar high-grade cartilage defects (ICRS grade 3-4). Studies addressing patient-reported outcomes, return to sports, or magnetic resonance imaging (MRI) at follow-up after isolated OAT procedures for patellar cartilage defects were included. Results: A total of 5 studies were included in this review. We were not able to perform a meta-analysis as no studies had available data. A total of 102 patients who received an isolated OAT for a patellar chondral defect were included in these 5 studies. All patients showed significant improvement at final follow-up based on the following patient-reported outcome scores: Lysholm, International Knee Documentation Committee, Kujala, Tegner, and 36-Item Short Form Health Survey. We found that 4 studies used MRI during the first postoperative year to assess osteochondral plug integration and positioning. The results demonstrated that most plugs were integrated and correctly positioned when evaluated at follow-up, conducted on average after 12 months. Whether patients were able to return to sports was queried in 2 of the included studies, revealing that patients could return to their previous level in most cases (Tegner score, 5-9 at 2 years after surgery). Conclusion: Results indicate that OAT is a safe and reliable technique to treat patellar high-grade osteochondral defects, allowing for significant improvement in patient-reported outcomes and return to sports.